BIOSENSORS FOR FAST DETECTION OF TOXIC COMPOUNDS - Camelia Bala; Lucian-Gabriel Zamfir; Lucian Rotariu (European Scientific Journal, ESJ, 2014)
Due to the fact that biosensors play a significant analytical role in agriculture, food safety, environmental and industrial monitoring we present an overview on the biosensor field, especially the design of the interface between the physical transducer and the biological recognition elements for the fast detection of pesticides. We will introduces novel concepts in the area of bioanalysis based on nanomaterials (carbon nanotubes) and composite based on nanomaterials in order to enhance the performance of the developed biosensors. Also, different immobilization procedures for biorecognition element will be presented. Technical description and analytical characterization of the biosensor will be detailed.